The Critical Role of Fillers in Composite Polymer Electrolytes for Lithium Battery - Yang, Xueying; Liu, Jiaxiang; Pei, Nanbiao; Chen, Zhiqiang; Li, Ruiyang; Fu, Lijun; Zhang, Peng; Zhao, Jinbao (Nano-Micro Letters, 2023)
With excellent energy densities and highly safe performance, solid-state lithium batteries (SSLBs) have been hailed as promising energy storage devices. Solid-state electrolyte is the core component of SSLBs and plays an essential role in the safety and electrochemical performance of the cells. Composite polymer electrolytes (CPEs) are considered as one of the most promising candidates among all solid-state electrolytes due to their excellent comprehensive performance. In this review, we briefly introduce the components of CPEs, such as the polymer matrix and the species of fillers, as well as the integration of fillers in the polymers. In particular, we focus on the two major obstacles that affect the development of CPEs: the low ionic conductivity of the electrolyte and high interfacial impedance. We provide insight into the factors influencing ionic conductivity, in terms of macroscopic and microscopic aspects, including the aggregated structure of the polymer, ion migration rate and carrier concentration. In addition, we also discuss the electrode–electrolyte interface and summarize methods for improving this interface. It is expected that this review will provide feasible solutions for modifying CPEs through further understanding of the ion conduction mechanism in CPEs and for improving the compatibility of the electrode–electrolyte interface. Highlights: 1 The mechanism of the change in lithium-ion transport behavior caused by the incorporation of inorganic fillers into the polymer matrix is reviewed. 2 The intrinsic factors of inorganic fillers to enhance the ionic conductivity of composite polymer electrolyte (CPEs) are investigated in depth. 3 The contribution of inorganic fillers to inhibit dendrite growth and side reactions in CPEs is summarized.